2019
DOI: 10.1093/condor/duz011
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative impacts of roads and energy infrastructure on grassland songbirds

Abstract: Comparing impacts of co-occurring anthropogenic features is necessary for regional planning and can help identify mechanisms of negative impacts of development on wildlife. Because of the vast abundance of anthropogenic features in the Northern Great Plains, their combined negative impacts on songbird habitat use (e.g., abundance) and productivity (e.g., nesting success and clutch size) could exacerbate the decline of songbird populations. We compared the cumulative effects of energy-related infrastructure (oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Abundance declined above a gas well density of 6 wells per section (with a range from 0 to 36 well pads per km 2 ). Clutch size increased as distance to natural gas wells increased, whereas no relationship was found between clutch size and distance to oil wells or to density of wells, and no relationships were found between nest success and distance to oil or natural gas wells or to density of wells (Daniel and Koper, 2019). Ludlow and others (2015) reported that Sprague's Pipit nest locations relative to oil and gas wells did not differ from random locations.…”
Section: Species' Response To Managementmentioning
confidence: 95%
See 4 more Smart Citations
“…Abundance declined above a gas well density of 6 wells per section (with a range from 0 to 36 well pads per km 2 ). Clutch size increased as distance to natural gas wells increased, whereas no relationship was found between clutch size and distance to oil wells or to density of wells, and no relationships were found between nest success and distance to oil or natural gas wells or to density of wells (Daniel and Koper, 2019). Ludlow and others (2015) reported that Sprague's Pipit nest locations relative to oil and gas wells did not differ from random locations.…”
Section: Species' Response To Managementmentioning
confidence: 95%
“…Fewer young were fledged from successful nests near trails than nests further from trails; proximity to roads did not influence density or nest success, and no relationship was found between frequency of brood parasitism (based on a combination of all parasitized nests for the suite of songbird species evaluated) and distance to gravel roads or trails. Bernath-Plaisted and and Daniel and Koper (2019) reported no relationship between nest success and distance to nearest road; however, Daniel and Koper (2019) reported that Sprague's Pipit abundance was lower near roads, whereas clutch size was higher near roads. In lightly to moderately grazed native prairies in Saskatchewan, Sprague's Pipits were significantly more abundant alongside trails (single pairs of wheel ruts visually indistinct from surrounding habitat in terms of plant structure and composition) than alongside roads (traveling surfaces with adjacent drainage ditches planted to smooth brome and ending with a fence 11-18 m from the traveling surface) (Sutter and others, 2000).…”
Section: Species' Response To Managementmentioning
confidence: 97%
See 3 more Smart Citations